2019
DOI: 10.4314/tjpr.v17i11.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of clinical effectiveness of paclitaxel and ursolic acid co-loaded liposomes as enhanced treatment for head and neck squamous cell carcinoma

Abstract: Purpose: To enhance the clinical effectiveness of paclitaxel (PTX) by co-delivery with ursolic acid (UA) for the treatment of head and neck cancer Methods: Co-loaded liposomes of PTX and UA (UA-PTX-LiP) were prepared by thin-film hydration method. Their size and loading efficiency were determined using dynamic light scattering (DLS) technique and high performance liquid chromatography (HPLC), respectively. The effectiveness of UA-PTX-LiP against HSC-3 human head and neck cancer cell-lines was compared with tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Likewise, it was observed that UA-PTX-LiP inhibited the growth of HSC-3 cancer cell line and increased cellular uptake that caused cell apoptosis more strongly than the chemotherapic administered alone or encapsulated. The more pronounced effect of the complex is believed to be due to the triterpene, ursolic acid, which is known to cause cancer cell apoptosis by inhibiting cyclooxygenase 2 [37].…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, it was observed that UA-PTX-LiP inhibited the growth of HSC-3 cancer cell line and increased cellular uptake that caused cell apoptosis more strongly than the chemotherapic administered alone or encapsulated. The more pronounced effect of the complex is believed to be due to the triterpene, ursolic acid, which is known to cause cancer cell apoptosis by inhibiting cyclooxygenase 2 [37].…”
Section: Resultsmentioning
confidence: 99%
“…The co-loading of UA was also experimented by Lv et al who combined the phytocompound with paclitaxel and loaded the mixture in stealth liposomes (UA-PTX-Lip) as potential treatment for head and neck squamous cell carcinoma. UA-PTX-Lip were prepared using the thin-film dispersion hydration method using hydrogenated soy phosphatidylcholine, cholesterol, and DSPE-PEG 2000 as lipid components; their anti-tumor activity was compared with paclitaxel liposomes (PTX-Lip) in vitro against HCS-3 cancer cells lines; the results showed that UA-PTX-Lip exhibited highly improved cytotoxicity on HCS-3 cells compared to PTX-Lip due to the presence of UA which exerts an increased oxidative effect on HSC-3 cells thus leading to an optimized apoptotic effect [279]. The combination drug obtained by linking UA and lamivudine (LMX) was prepared and evaluated for its anti-hepatitis B and hepatoprotective activity.…”
Section: Ursolic Acidmentioning
confidence: 99%